Significant Microsynteny with New Evolutionary Highlights Is Detected through Comparative Genomic Sequence Analysis of Maize CCCH IX Gene Subfamily - Wei-Jun Chen; Yang Zhao; Xiao-Jian Peng; Qing Dong; Jing Jin; Wei Zhou; Bei-Jiu Cheng; Qing Ma (International Journal of Genomics)
CCCH zinc finger proteins, which are characterized by the presence of three cysteine residues and one histidine residue, play important roles in RNA processing in plants. Subfamily IX CCCH proteins were recently shown to function in stress tolerances. In this study, we analyzed CCCH IX genes in Zea mays, Oryza sativa, and Sorghum bicolor. These genes, which are almost intronless, were divided into four groups based on phylogenetic analysis. Microsynteny analysis revealed microsynteny in regions of some gene pairs, indicating that segmental duplication has played an important role in the expansion of this gene family. In addition, we calculated the dates of duplication by Ks analysis, finding that all microsynteny blocks were formed after the monocot-eudicot divergence. We found that deletions, multiplications, and inversions were shown to have occurred over the course of evolution. Moreover, the Ka/Ks ratios indicated that the genes in these three grass species are under strong purifying selection. Finally, we investigated the evolutionary patterns of some gene pairs conferring tolerance to abiotic stress, laying the foundation for future functional studies of these transcription factors.